Penerapan Psikologi Desain pada Elemen Desain Interior - Setiawan, Budi; Ruki, Ulli Aulia (Humaniora, 2014)
One of main interior designer’s assignments is to solve the problem within the facility. Problems may occur because the activities of design decision had done or will be done on the facility are not maximized. This problem can be reduced by rethinking the design through psychology design. Utilizing psychology design will help designer decide a better judgment of objects that affects the person using it in routine. The example of interior objects is wall, door, floor, color, and other elements of interior. Desk research method was used to support this article trough data collection from books and other professional institution websites. At the end, the conclusion of this article does not directly impact the result since it took time to persuade judgment of the user, but positively it will construct designer to rethink the design object.